Combinatorial delivery of CPI444 and vatalanib loaded on PEGylated graphene oxide as an effective nanoformulation to target glioblastoma multiforme: In vitro evaluation - Mishra, Vishnu S.; Patil, Sachin; Reddy, Puli Chandramouli; Lochab, Bimlesh (Frontiers in Oncology, 2022)
Glioblastoma multiforme (GBM) is known as the primary malignant and most devastating form of tumor found in the central nervous system of the adult population. The active pharmaceutical component in current chemotherapies is mostly hydrophobic and poorly water-soluble, which hampers clinical implications. Nanodrug formulations using nanocarriers loaded with such drugs assisted in water dispersibility, improved cellular permeability, and drug efficacy at a low dose, thus adds to the overall practical value. Herein, we successfully developed a water-dispersible and biocompatible nanocargo (GO-PEG) based on covalently modified graphene oxide (GO) with 6-armed poly(ethylene glycol) amine dendrimer for effective loading of the two hydrophobic anticancer drug molecules, CPI444 and Vatalianib. These drug molecules target adenosine receptor (A2AR), vascular endothelial growth factor receptor (VEGFR), platelet-derived growth factor receptor (PDGFR), and type III stem cell receptor tyrosine kinase (c-KIT), which plays a crucial role in cancers. The effective cellular delivery of the drugs when loaded on GO-PEG is accounted to the increased permeability of the drug-nanoconjugate formulation. We observed that this combinatorial drug treatment with nanocargo resulted in a significant reduction in the overall cell survival as supported by reduced calcium levels and stem cell markers such as Oct4 and Nanog that are one of the prime factors for GBM stem cell proliferation. Furthermore, reduced expression of CD24 upon treatment with nanoformulation impeded cellular migration. Cellular assays confirmed inhibition in cell proliferation, migration, angiogenic potential of GBM treated with GO-PEG-Drug conjugates. Ultimately, GBM U87 cells assumed programmed cell death at very low concentration due to nanocarrier mediated drug delivery along with the chosen combination of drugs. Together, the present study demonstrated the advantage of GO-PEG mediated combined delivery of CPI444 and Vatalanib drugs with increased permeability, a three-pronged combinatorial strategy towards effective GBM treatment.